The Role of Applying Governance Principles in Improving Decision-Making in Algerian Sports Clubs (A Field Study on the Clubs of the Regional Football League of Annaba) - طهيري مدمذ ألامين; لعجال يحي (sports creativity, 2025)
This study aims to clarify the role of applying governance principles in improving decision-making in sports clubs in the Regional Football League of Annaba in particular, and in Algerian sports clubs in general. This is achieved by presenting the theoretical and practical framework of the study using the descriptive-analytical approach and administering a questionnaire to the managements of clubs affiliated with the Regional Football League of Annaba. The study reached a set of results, the most important of which is that the application of governance principles has a medium-level effect on improving decision-making in sports clubs in the Regional Football League of Annaba